Universal dynamics of zero-momentum to plane-wave transition in spin–orbit coupled Bose–Einstein condensates. (15th May 2018) - Ye, Qinzhou; Wu, Shuyuan; Jiang, Xunda; Lee, Chaohong
Abstract: We investigate the universal spatiotemporal dynamics in spin–orbit coupled Bose–Einstein condensates which are driven from the zero-momentum phase to the plane-wave phase. The excitation spectrum reveals that, at the critical point, the Landau critical velocity vanishes and the correlation length diverges. Therefore, according to the Kibble–Zurek mechanism, spatial domains will spontaneously appear in such a quench through the critical point. By simulating the real-time dynamics, we numerically extract the static correlation length critical exponent and the dynamic critical exponent z from the scalings of the temporal bifurcation delay and the spatial domain number. The numerical scalings consist well with the analytical ones obtained by analyzing the excitation spectrum.